Pendidikan Biologi di SMA Indonesia: Kajian Kebijakan Buku Teks dan Kurikulum - Hastangka Hastangka; Latifa Nuraini (BIOEDUSCIENCE, 2023)
Background: Biology education has a vital role in scientific development, strengthening the position of biology education for sustainable development and advancing biological science. During this time, biology materials developed rapidly. Methods: Writing the word Abstract using Cambria 9pt, in italics. The Abstract consists of 150-250 words written in one paragraph, containing the essence of the manuscript, background, research objectives, methods, results, and conclusions. Results: Biology education material that has developed since there were three changes to the curriculum in Indonesia after the issuance of Law Number 20 of 2003 concerning the National Education System does not appear to have shown any significant changes specifically in the subject matter for class X SMA. Curriculum policies and the development of textbooks in Indonesia focus more on and continue the material in the previous curriculum since the emergence of the competency-based curriculum (2004). Conclusions: The development of biology education in Indonesia from materials, textbooks, and curriculum policies does not show a significant change and development in the development of biology science for class X SMA. This study concludes that textbooks and curriculum policies have not been able to change the perspective and substance of the direction of learning biology in Indonesia. So the portrait of the capacity and insight of the Indonesian generation's knowledge about biology can be seen from the curriculum policies and the existing materials.